Children, Schooling, and COVID-19 - Chloë Brushwood Rose; Morgan Bimm (University of Windsor, 2021)
This paper offers a review of the research on children, schooling, and disasters in order to identify critical information for the field of education and the practice of educational research in response to the COVID-19 pandemic. What do we know about the experiences of children and their interactions with schools during and following a natural disaster like COVID-19? The review answers this question and both identifies areas of study that need further attention and explores critical methodological approaches for further educational research. Areas of the research reviewed include children's experiences of disaster, the educational impacts of disaster, the role of schools and teachers in responding to disaster, and methodological considerations for further research. The authors conclude that educational research can play a critical role in recovery efforts for children, teachers, and schools.